2009
DOI: 10.1007/s10470-009-9427-2
|View full text |Cite
|
Sign up to set email alerts
|

A 3.3 V 72.2 Mbit/s 802.11n WLAN transformer-based power amplifier in 65 nm CMOS

Abstract: This paper describes the design of a power amplifier (PA) for 802.11n WLAN fabricated in 65 nm CMOS technology. The PA utilizes 3.3 V thick gate oxide (5.2 nm) transistors and a two-stage differential configuration with integrated transformers for input and interstage matching. A methodology used to extract the layout parasitics from electromagnetic (EM) simulations is described. For a 72.2 Mbit/s, 64-QAM, 802.11n OFDM signal at an average and peak output power of 11.6 and 19.6 dBm, respectively, the measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The average drain capacitance of the device was estimated in the off-state [10], while V DS was swept from 0V to 3V, and was equal to 0.7pF/1000µm transistor width. To reduce the resistive losses at the drains and sources, several metal layers were stacked on top of each other as described in [11], but this also adds parasitic capacitance between gate, drain, and source. The parasitic layout capacitances C gd,par and C ds,par ( Fig.…”
Section: Design and Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The average drain capacitance of the device was estimated in the off-state [10], while V DS was swept from 0V to 3V, and was equal to 0.7pF/1000µm transistor width. To reduce the resistive losses at the drains and sources, several metal layers were stacked on top of each other as described in [11], but this also adds parasitic capacitance between gate, drain, and source. The parasitic layout capacitances C gd,par and C ds,par ( Fig.…”
Section: Design and Implementationmentioning
confidence: 99%
“…Simulations of the PA indicated that the peak drain voltage reached levels of 2.5xVDD (3.5V) for a supply voltage of 1.4V as seen in Fig. 7, where the simulation model includes layout parasitics extracted in EM simulations [11], bond wires, PCB tracks, and S-parameters of the lumped matching components. The simulated waveforms can be expected in case the PA is matched identical to the simulated load impedance.…”
Section: A Simulationsmentioning
confidence: 99%